Terpenes from Euphorbia antiquorum and Their in Vitro Anti‐HIV Activity. Issue 5 (6th May 2018) - Dong, Miao; Chen, Xuan‐Qin; Chen, Chin‐Ho; Li, Rong‐Tao
Abstract : Three new compounds (1 –3 ), including two euphane type triterpenes, 24, 24‐dimethoxy‐25, 26, 27‐trinoreuphan‐3 β ‐ol (1 ) and (24 S )‐24‐hydroperoxyeupha‐8, 25‐dien‐3 β ‐ol (2 ), and an ent ‐atisine diterpene, ent ‐atisane‐3 α, 16 α, 17‐triol (3 ), were isolated from an acetone extract of the stems of Euphorbia antiquorum, together with eight known diterpenes (4 –11 ). The structures of compounds (1 –11 ) were elucidated using NMR and MS spectroscopic methods. Compound7 showed moderate activity against HIV‐1 replication in vitro (EC50 = 1.38 μm ). Abstract :